CORRELATION OF KNOWLEDGE WITH NURSE CONFIDENCE IN FOLLOWING UP EARLY WARNING SCORES IN HOSPITALIZATION - Megawati, Sri Wulan; Martilengga, Vivop; HHK, Nur Intan; Yusuf, Heri Handiana (Karsa Husada Health Institute Garut, 2023)
Early Warning Score (EWS) is used to assess the physiological changes of patients in hospitalization where deterioration of the patient's condition can occur so nurses must have the knowledge and confidence to follow up the EWS. Nurses' knowledge and skills in identifying patient deterioration greatly affect the implementation of EWS. Nurse confidence affects the quality of service so it is necessary to explore how nurses' knowledge and confidence have been in the inpatient room which is the focus of this study. The purpose of this study was to analyze the correlation between knowledge and nurses' confidence in following up EWS in inpatient settings. The research design is quantitative with a correlational approach. Sampling was done by purposive sampling technique where the sample was 93 nurses. This research instrument consists of a demographic data questionnaire, EWS knowledge and nurse confidence. Data collection was carried out by distributing questionnaire links via g-form. Data analysis using the Spearman Test. The results obtained were that most respondents (68.8%) had sufficient knowledge, most respondents (61.3%) had high confidence and there was no correlation between knowledge and nurse confidence in following up EWS with a Sig (2-tailed) value of .330. It is necessary to study other factors that affect nurses' confidence in following up EWS with a larger number of samples.